TEACHER PERSPECTIVE ON THE PROBLEM OF IMPLEMENTING MERDEKA BELAJAR CURRICULUM IN SMKN 3 PEKALONGAN A NARRATIVE INQUIRY: Abstrak, Abstract, Introduction, Methodology, Findings and Disscussion, Conclusion, References - Candra Kirana, Fortunelia Galuh (LPPM Universitas Pekalongan, 2024)
The Merdeka Curriculum has many intracurricular learning options and is designed to be more flexible for teachers and students. Therefore, This research aims to describe the teachers' perspectives on the problems implementation of the Merdeka curriculum at school. This research is a case study research that uses qualitative methods with a narrative inquiry approach. The results of this study show that there are problems that become obstacles for teachers at school. In this Merdeka Belajar curriculum, teachers must be able to adapt to curriculum changes and rapid technological developments. The results of this study indicate that English teachers at SMK N 3 Pekalongan have difficulty in applying the Merdeka Belajar Curriculum to the development of Learning Modules, formulating Learning Tools into a flow of Learning Objectives, teachers' ignorance of differentiated learning, lack of Merdeka Curriculum training.